Playing with political fire: Cameron, the Conservatives and the EU referendum. Issue 3 (December 2015) - Curtice, John
Abstract : John Curtice sketches out the polling data on the EU referendum question, and finds a nation divided. With the prime minister's negotiation demands now in the open, he asks, has Cameron set the bar too low to secure the support of his own party and his voters?